Autonomia pedagógica da escola na história das ideias e políticas públicas da educação brasileira - Vilella, Mariana (2022)
The thesis investigates the assertion of pedagogical autonomy of public schools in the history of ideas and public policies in Brazilian education, between 1932 and 2014. Initially, pedagogical autonomy is conceptualized as a guiding principle of national education, which recognizes the capacity of each school to author its political-pedagogical project, without removing the preponderant role of the State in providing and organizing public education. Then, it investigates how this idea was constituted in the history of Brazilian education. It is a qualitative research, using literature review methods and document analysis, with emphasis on the examination of educational legislation. The selection of bibliography and legislation was based on a specific theoretical framework, with emphasis on Saviani and Cury, and other specific references according to the historical moments and documents examined. The construction of a timeline in which it indicates and justifies the political and legal frameworks constituting the idea of pedagogical autonomy is the main result of the research. Secondary findings come from this construction and demonstrate that the principle of pedagogical autonomy is shaped by a combination of political, legal and pedagogical factors that prevail in each historical moment. The 1932 “Manifesto dos Pioneiros da Educação Nova” (“1932 Manifest”) is the starting point of the argument, because it proposes an agenda for a nationally coordinated educational system that guarantees diversity in unity. However, the political and legal instability and the discontinuity of democracy, with the establishment of authoritarian regimes, impacted the pedagogical mentality of the time, as well as the organization of public education and, consequently, the possibilities and limits for schools’ autonomy. Moments of redemocratization, on the other hand, brought to light proposals for a autonomy-based national educational system. The thesis highlights the 1988 Federal Constitution, when pedagogical autonomy was established as a constitutional principle that ordered Brazilian education. The final milestone of the thesis is the 2014 National Education Plan (Law n. 13.005/2014), when the legal affirmation of autonomy meets the pedagogical concept of integral education, which elevates the autonomy of schools to the essence of a national educational project. The agenda of integral education incorporated into public policies took up, in general, the proposals present in the 1932 Manifest, closing the historical arc of the thesis. The research focused on the relationship between pedagogical autonomy and the right to education, not only listing legal provisions, but seeking to clarify the meaning and historical context of the norms embedded in the Brazilians national educational projects, reflecting upon how they shape the possibility of schools’ institutional autonomy, a topic that remains challenging for the elaboration and implementation of public policies for Brazilian schools